Early occupational exposure to lead on neutrophil-to-lymphocyte ratio and genotoxicity. (June 2021) - Meng, Yu; Wang, Kan; Wang, Tuanwei; Tu, Yuting; Gong, Shiyang; Zhang, Yunxia; Zhang, Guanghui; Au, William; Christiani, David C.; Xia, Zhao-lin
Highlights: There exist dose-response relationships between Pb exposure and genotoxicity. Neutrophil-to-lymphocyte ratio is positively associated with blood Pb levels. There is a significantly positive association between NLR and Comet parameter. Comet parameter mediates 15% of the effect of Pb on elevated NLR. Abstract: Background: Lead (Pb) is known to induce detrimental health effects in exposed populations, including hematotoxicity and genotoxicity. Complete blood count (CBC) is a cost-effective and easy way to determine toxicity, and variations in proportion of different types of leukocytes: neutrophil-to-lymphocyte ratio (NLR) and lymphocyte-to-monocyte ratio (LMR) are further evidence of hematotoxicity. However, few studies have been conducted to systematically evaluate effects of occupational Pb exposure on NLR and LMR, and their associations with genotoxicity. Objectives: Our study was aimed to systematically assess the effects of current occupational Pb exposure on NLR and LMR, and their associations with genotoxicity. Methods: Our investigation was performed on 1176 workers from a newly built battery factory in North China. The workers had just entered their current job position in recent years and most of them had no previous history of occupational exposure to Pb. Blood lead levels (BLLs) and leukocytes indices were detected for all participants. Cytokinesis-blocked micronucleus assay (MN; n = 675) and alkaline comet assay (% tail DNA; n = 869) were used to assess genotoxicity. Multivariate linear and Poisson regression analyses were conducted to examine associations between leukocytes indices, genotoxic biomarkers and BLLs with adjustment for covariates. Spearman correlation and mediation analyses were used to investigate relationships between NLR and genotoxicity. Results: Among all the exposed workers, NLR increased with increasing BLLs. However, WBC and LMR did not change significantly. Significant and dose-dependent increases in both MN frequencies and % tail DNA were observed among groups with different exposure doses. Compared with the normal NLR group (1.48 ≤ NLR < 4.58), the high NLR group (NLR ≥ 4.58) had higher % tail DNA. In addition, there was a significant and positive association between NLR and % tail DNA among all the workers, and % tail DNA mediated 15% of the effect of Pb on increasing NLR. Conclusion: Our large-scale population study shows that Pb exposure increased NLR and induced genotoxicity. There was an association between elevated NLR and DNA damage. In addition, the mediation effect of % tail DNA on the relationship between BLLs and NLR provided mechanistic evidence that certain mechanisms, e.g. inflammation, may be involved in elevation of NLR from Pb exposure. Therefore, NLR may be a convenient and sensitive biomarker for indication of Pb toxicity. Further studies are needed to validate the proposed mechanism and NLR as a biomarker.